Autophagy-dependent cell cycle arrest in esophageal cancer cells exposed to dihydroartemisinin - Qiang Ma; Hebin Liao; Lei Xu; Qingrong Li; Jiang Zou; Ru Sun; Dan Xiao; Chang Liu; Wenjie Pu; Jibing Cheng; Xi Zhou; Guangcheng Huang; et al. (BMC, 2020)
Abstract Background Dihydroartemisinin (DHA), a derivate of artemisinin, is an effective antimalarial agent. DHA has been shown to exert anticancer activities to numerous cancer cells in the past few years, while the exact molecular mechanisms remain to be elucidated, especially in esophageal cancer. Methods Crystal violet assay was conducted to determine the cell viability of human esophageal cancer cell line Eca109 treated with DHA. Tumor-bearing nude mice were employed to evaluate the anticancer effect of DHA in vivo. Soft agar and crystal violet assays were used to measure the tumorigenicity of Eca109 cells. Flow cytometry was performed to evaluate ROS or cell cycle distribution. GFP-LC3 plasmids were delivered into Eca109 cells to visualize autophagy induced by DHA under a fluorescence microscope. The mRNA and protein levels of each gene were tested by qRT-PCR and western blot, respectively. Results Our results proved that DHA significantly reduced the viability of Eca109 cells in a dose- and time-dependent manner. Further investigation showed that DHA evidently induced cell cycle arrest at the G2/M phase in Eca109 cells. Mechanistically, DHA induced intracellular ROS generation and autophagy in Eca109 cells, while blocking ROS by an antioxidant NAC obviously inhibited autophagy. Furthermore, we found that telomere shelterin component TRF2 was down-regulated in Eca109 cells exposed to DHA through autophagy-dependent degradation, which could be rescued after autophagy was blocked by ROS inhibition. Moreover, the DNA damage response (DDR) was induced obviously in DHA treated cells. To further explore whether ROS or autophagy played a vital role in DHA induced cell cycle arrest, the cell cycle distribution of Eca109 cells was evaluated after ROS or autophagy blocking, and the results showed that autophagy, but not ROS, was essential for cell cycle arrest in DHA treated cells. Conclusion Taken together, DHA showed anticancer effect on esophageal cancer cells through autophagy-dependent cell cycle arrest at the G2/M phase, which unveiled a novel mechanism of DHA as a chemotherapeutic agent, and the degradation of TRF2 followed by DDR might be responsible for this cell phenotype.